Identification of a novel family B DNA polymerase from Enterococcus phage IME199 and its overproduction in Escherichia coli BL21(DE3) - Pengjun Han; Huahao Fan; Yigang Tong (Microbial Cell Factories, 2023)
Abstract Background Identification and characterization of novel, faithful and processive DNA polymerases is a driving force in the development of DNA amplification methods. Purification of proteins from natural phages is often time-consuming, cumbersome and low yielding. Escherichia coli is a host bacterium widely used for the production of recombinant proteins, is the cell factory of choice for in vitro studies of phage protein function. Results We expressed the gene encoding Enterococcus faecium phage IME199 DNA polymerase (IME199 DNAP) in Escherichia coli BL21(DE3), and characterized protein function. IME199 DNAP has 3′-5′ exonuclease activity, but does not have 5′-3′ exonuclease activity. In addition, IME199 DNAP has dNTP-dependent 5′-3′ polymerase activity and can amplify DNA at 15–35 °C and a pH range of 5.5–9.5. The amino acid residues Asp30, Glu32, Asp112 and Asp251 are the 3′-5′ exonuclease active sites of IME199 DNAP, while residues Asp596 and Tyr639 are essential for DNA synthesis by IME199 DNAP. More importantly, the IME199 DNAP has strand displacement and processive synthesis capabilities, and can perform rolling circle amplification and multiple displacement amplification with very low error rates (approximately 3.67 × 10–6). Conclusions A novel family B DNA polymerase was successfully overproduced in Escherichia coli BL21(DE3). Based on the characterized properties, IME199 DNAP is expected to be developed as a high-fidelity polymerase for DNA amplification at room temperature.